Pemanfaatan Media Promosi Elektronik Mendukung Lahirnya Posdaya Dalam Pemberdayaan Pendidikan Dan Kesehatan Masyarakat - Faisal Piliang; Desie Risnawati (Sekolah Tinggi Teknik - PLN, 2016)
Today there was a transition of the media campaign carried out manually into a decision to utilize the electronic media campaign, using information communication technology (ICT) implementation. In this research discusses the development and utilization of electronic media campaign to support the birth “Posdaya” in the empowerment of education and public health, by using technology ICT (Information Communication Technology) in the form of electronic records page. Research methods and data collection at this research is using the research, and field work research. In this research, the development of pages as promotion of electronic technology using Information Communication Technology (ICT) can be implemented as a public service and a media campaign in order to inform about the birth of “Posdaya” in order to empower the education and public health, and for further research is necessary to develop implementation strategies for the empowerment of environment and economics.